The effects of care bundles on patient outcomes: a systematic review and meta-analysis - Jacqueline F. Lavallée; Trish A. Gray; Jo Dumville; Wanda Russell; Nicky Cullum (Implementation Science, 2017)
Abstract Background Care bundles are a set of three to five evidence-informed practices performed collectively and reliably to improve the quality of care. Care bundles are used widely across healthcare settings with the aim of preventing and managing different health conditions. This is the first systematic review designed to determine the effects of care bundles on patient outcomes and the behaviour of healthcare workers in relation to fidelity with care bundles. Methods This systematic review is reported in line with the PRISMA statement for reporting systematic reviews and meta-analyses. A total of 5796 abstracts were retrieved through a systematic search for articles published between January 1, 2001, to February 4, 2017, in the Cochrane Central Register for Controlled Trials, MEDLINE, EMBASE, British Nursing Index, CINAHL, PsychInfo, British Library, Conference Proceeding Citation Index, OpenGrey trials (including cluster-randomised trials) and non-randomised studies (comprising controlled before-after studies, interrupted time series, cohort studies) of care bundles for any health condition and any healthcare settings were considered. Following the removal of duplicated studies, two reviewers independently screen 3134 records. Three authors performed data extraction independently. We compared the care bundles with usual care to evaluate the effects of care bundles on the risk of negative patient outcomes. Random-effect models were used to further explore the effects of subgroups. Results In total, 37 studies (6 randomised trials, 31 controlled before-after studies) were eligible for inclusion. The effect of care bundles on patient outcomes is uncertain. For randomised trial data, the pooled relative risk of negative effects between care bundle and control groups was 0.97 [95% CI 0.71 to 1.34; 2049 participants]. The relative risk of negative patient outcomes from controlled before-after studies favoured the care bundle treated groups (0.66 [95% CI 0.59 to 0.75; 119,178 participants]). However, using GRADE, we assessed the certainty of all of the evidence to be very low (downgraded for risk of bias, inconsistency, indirectness). Conclusions Very low quality evidence from controlled before-after studies suggests that care bundles may reduce the risk of negative outcomes when compared with usual care. By contrast, the better quality evidence from six randomised trials is more uncertain. Trial registration PROSPERO, CRD42016033175